Risk, Firm Heterogeneity, and Dynamics of FDI Entry - CHANG, Pao Li (Institutional Knowledge at Singapore Management University, 2009)
We study the dynamics of FDI entry under a setting with firm heterogeneity and FDI uncertainty. The risk of FDI failure depends positively on the complexity of production technology, negatively on the quality of infrastructure in the host country, and evolves over time with the extent of knowledge diffusion. The incorporation of FDI uncertainty leads to a non-monotonic relationship between technology complexity and the timing of FDI entry: firms with intermediate technology levels lead the first wave of FDI, which helps lower the investment uncertainty facing subsequent investors and induces a wider range of FDI entry in the second period. We prove the existence of a stable steady state for this self-reinforcing process and identify how the extensive margin of FDI at the steady state varies with the host and home country characteristics. Supporting empirical observations are also provided.